Micro-focus CT in-situ marking device and method

Through the microfocus CT in-situ marking device and method, the internal structural changes and defects of ceramic matrix composite materials under high temperature water and oxygen environment are accurately detected and evaluated, solving the problems of high detection cost and low efficiency in the prior art, and achieving efficient and accurate detection results.

CN119827532APending Publication Date: 2025-04-15WUZHEN LABORATORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411956805.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

It is difficult for the prior art to accurately detect and evaluate the internal structural changes and defects of ceramic matrix composites in high temperature water-oxygen environments, especially in the study of block materials, direct detection takes a long time and is costly.

Method used

A micro-focus CT in situ marking device and method is provided. Through the combination of a local position marking rod and a micro-focus CT sample table, the marking of a certain position of the micro-composite material and the CT scanning analysis before and after the assessment in a high-temperature water-oxygen environment is realized.

Benefits of technology

Accurate detection and evaluation of internal structural changes and defects of ceramic matrix composite materials in the same location under high temperature water and oxygen environment, reducing detection costs and improving detection efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005216509690000011
    Figure HDA0005216509690000011
  • Figure HDA0005216509690000012
    Figure HDA0005216509690000012
  • Figure HDA0005216509690000021
    Figure HDA0005216509690000021
Patent Text Reader

Abstract

The invention relates to the field of materials, in particular to a microfocus CT in-situ marking device and method. The method comprises a micro-focus CT sample table capable of loading a micro composite material sample, a sample local position marking rod and a fixing method thereof. According to the micro-focus CT sample table capable of loading the micro composite material, two independent cylindrical hollow spaces and a cuboid opening are formed in the CT sample table. According to the method, a certain position of the micro composite material is marked, so that micro-focus CT scanning and analysis on the same position of the micro composite material before and after high-temperature water-oxygen environment treatment are realized, and the influence of high-temperature water-oxygen treatment on the internal structure of the micro composite material and the change of defects of the micro composite material are researched more accurately and specifically.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a micro-focus CT in-situ marking device and method. Background Art

[0002] Ceramic matrix composites (CMC) have become potential materials for high-temperature thermal structural applications due to their excellent properties such as high temperature resistance, low density, oxidation resistance, and high strength. When ceramic matrix composites are used in high-temperature structural materials such as aircraft engines, aircraft thermal protection components, and nuclear reactors, the materials are subject to high temperature, thermal stress, and oxidative environment corrosion during their service, which leads to a sharp decrease in the stability of the components and even failure. Therefore, it is crucial to study the effects of water-oxygen coupling environment, temperature, time, and other factors on materials under high-temperature service conditions for the research and application of ceramic matrix composite high-temperature structural parts.

[0003] After the ceramic matrix composite material is tested in a high-temperature water-oxygen coupling environment, its internal structure has a key influence on the performance of the final material. Therefore, accurate detection and evaluation of the internal quality of ceramic matrix composite materials is crucial. Microfocus CT is an important means to observe and detect the internal structure of ceramic matrix composite materials. It can effectively characterize internal defects at the micro-nano scale. Its high resolution, comprehensiveness and three-dimensional visualization provide accurate and intuitive information for the analysis of key features such as internal defects, fiber distribution and geometric parameters of materials.

[0004] The research on high-temperature thermal structural parts of ceramic-based composites requires consideration of multiple factors such as temperature, time, and water-oxygen coupling environment. However, it takes a long time and is costly to directly study bulk ceramic-based composites. Since bulk ceramic-based composites are composed of multiple fiber bundles with different directions and arrangements, and the micro-composite specimens composed of a single fiber bundle and a matrix correspond to the basic scale of bulk composites, and the failure mechanism and damage law of unidirectional micro-composites in a high-temperature water-oxygen coupling environment are very similar to those of bulk composites, many scholars currently use micro-composites made at a lower cost to characterize their structure and performance in different high-temperature water-oxygen environments. In order to more accurately observe the changes in the internal structure and defects that occur at the same position of the micro-composite material after high-temperature water-oxygen testing. For example Figure 1 The schematic diagram of loading samples on the sample stage of the CT equipment shown in the figure uses double-sided tape to stick and fix the sample to the stage of the CT equipment. This method cannot directly mark a certain position of the sample. When the micro-composite material is pasted and fixed on the sample stage of the CT equipment again after high-temperature water and oxygen testing, the sample will be inverted or cannot be directly found in the same position. Summary of the invention

[0005] In view of this, the present invention provides a micro-focus CT in-situ marking device and method. The method marks a certain position of a micro-composite material, thereby realizing micro-focus CT scanning and analysis of the same position of the micro-composite material before and after being treated in a high-temperature water-oxygen environment, thereby more accurately and more specifically studying the influence of high-temperature water-oxygen treatment on the internal structure of the micro-composite material and the changes in its defects.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides a micro-focus in-situ marking device, the micro-focus in-situ marking device comprising a sample local position marking rod and a micro-focus CT sample stage;

[0008] The material of the sample local position marking rod includes but is not limited to a material that is resistant to high temperature oxidation; the shape of the sample local position marking rod includes but is not limited to a cuboid; the number of the sample local position marking rods includes at least 1; the height of the sample local position marking rod includes 5 to 15 mm;

[0009] The material of the micro-focus CT sample stage includes but is not limited to a material resistant to high temperature oxidation; the micro-focus CT sample stage includes an independent hollow space and an opening; the diameter of the micro-focus CT sample stage includes 10 to 20 mm, and the thickness includes 3 to 6 mm;

[0010] The microfocus CT sample stage, the opening and the sample local position marking rod mark the position of the sample from three angles;

[0011] The sample is fixed at the center of the microfocus CT sample stage;

[0012] The opening marks the position of the microfocus CT sample stage;

[0013] The sample local position marking rod marks the height of the sample when it is scanned;

[0014] The independent hollow space and the opening penetrate the microfocus CT sample stage;

[0015] The number of the independent hollow spaces includes at least 2; the shape of the independent hollow spaces includes a cylinder; the diameter of the independent hollow spaces includes 1 to 4 mm;

[0016] The number of the openings includes at least 1; the shape of the opening includes a cuboid;

[0017] In some specific embodiments of the present invention, the material of the sample local position marking rod includes but is not limited to aluminum oxide or silicon carbide;

[0018] The height of the sample local position marking rod includes 5mm, 12mm or 15mm;

[0019] The material of the microfocus CT sample stage includes but is not limited to aluminum oxide or silicon carbide;

[0020] The diameter of the microfocus CT sample stage includes 10 mm, 15 mm or 20 mm, and the thickness includes 3 mm, 4 mm or 6 mm;

[0021] The diameter of the independent hollow space includes 1mm, 3mm or 4mm;

[0022] Preferably, the diameter of the microfocus CT sample stage is 10 mm and the thickness is 6 mm; or

[0023] The diameter of the microfocus CT sample stage is 20 mm or less, and the thickness is 4 mm or less; or

[0024] The diameter of the microfocus CT sample stage is 15 mm, and the thickness is 3 mm.

[0025] In a second aspect, the present invention further provides an application of the micro-focus in-situ marking device in any of the following:

[0026] (I), micro-focus in situ labeling; and / or

[0027] (II) characterizing the structure and / or properties of the composite material;

[0028] The composite material includes but is not limited to a micro-composite material or a ceramic-based composite material;

[0029] The structure and / or performance of the composite material includes but is not limited to the structure and / or performance of the composite material at the same position before and after being subjected to high temperature and / or water-oxygen environment assessment;

[0030] The high temperature ranges from 800 to 1200° C.; the total flow rate of water vapor and oxygen in the water-oxygen environment ranges from 150 to 2000 mL / min; and the assessment time ranges from 1 to 40 hours.

[0031] In some specific embodiments of the present invention, the micro-composite material includes but is not limited to SiCf / BN / SiC micro-composite material; the ceramic-based composite material includes but is not limited to Cf / SiC ceramic-based composite material;

[0032] The high temperature includes 800°C, 1100°C or 1200°C; the total flow rate of water vapor and oxygen in the water-oxygen environment includes 150mL / min, 600mL / min or 2000mL / min; the test time includes 5h, 20h or 40h;

[0033] Preferably, the water vapor flow rate includes 1500 mL / min, and the oxygen flow rate includes 500 mL / min; or the water vapor flow rate includes 100 mL / min, and the oxygen flow rate includes 50 mL / min; or the water vapor flow rate includes 300 mL / min, and the oxygen flow rate includes 300 mL / min.

[0034] In a third aspect, the present invention further provides a microfocus CT in-situ marking method, based on the device, the method comprises the following steps:

[0035] Step 1, inserting the sample and the sample local position marking rod into the independent hollow space of the microfocus CT sample stage respectively, filling the gap position in the independent hollow space with slurry, heating, causing curing and / or cracking reaction, and fixing the sample and / or the sample local position marking rod to the microfocus CT sample stage respectively;

[0036] Step 2, record the scanning position and the position mark height of the sample (the height of the sample is marked with the height at the top of the marking rod, that is, the top of the marking rod is scanned each time to achieve observation of the same position), perform micro-focus CT scanning, and obtain a CT scan image of the sample before processing;

[0037] Step 3, placing the sample in a high temperature and / or water-oxygen environment for assessment, and performing a micro-focus CT scan on the same position of the sample mark according to the scanning orientation and the sample position mark height recorded in step 2 to obtain a CT scan image after assessment;

[0038] The high temperature includes 800 to 1200° C.; the total flow rate of water vapor and oxygen in the water-oxygen environment includes 150 to 2000 mL / min; the assessment time includes 1 to 40 hours;

[0039] Step 4: Compare the CT scan image of the sample before treatment obtained in step 2 with the CT scan image after assessment obtained in step 3, and analyze.

[0040] In some specific embodiments of the present invention, the ingredients of the slurry in step 1 include resin and ceramic powder; the ratio of the resin to the ceramic powder is 1:5 to 1:3;

[0041] Preferably, the ratio of the resin to the ceramic powder includes 1:3, 1:4 or 1:5;

[0042] The slurry preparation step includes: weighing the resin and the ceramic powder according to a proportion and stirring them evenly;

[0043] The resin includes but is not limited to polycarbosilane or phenolic resin; the ceramic powder includes but is not limited to silicon carbide.

[0044] In some specific embodiments of the present invention, the heating rate in step 1 includes but is not limited to 10°C / min, the heating temperature includes but is not limited to 120°C, and the time for which the microfocus CT sample stage is placed at the temperature includes but is not limited to 30 minutes;

[0045] The sample in step 1 comprises a composite material;

[0046] The composite material includes but is not limited to a micro-composite material or a ceramic-based composite material;

[0047] Preferably, the micro-composite material includes but is not limited to SiCf / BN / SiC micro-composite material;

[0048] Preferably, the ceramic-based composite material includes but is not limited to Cf / SiC ceramic-based composite material.

[0049] In some specific embodiments of the present invention, the scanning orientation in step 2 includes the position of the sample in the X-axis direction marked by the center of the microfocus CT sample stage and the position of the sample in the Y-axis direction marked by the opening; the position mark height of the sample includes the position of the sample in the Z-axis direction marked by the sample local position mark rod, thereby achieving three angle marks of the sample position;

[0050] The parameters of the microfocus CT scan in step 2 include: scanning mode bin2, exposure time 1 second, voltage 80 kV and power 10 W in air.

[0051] In some specific embodiments of the present invention, the high temperature in step 3 includes 800° C., 1100° C. or 1200° C.;

[0052] The total flow rate of water vapor and oxygen in the water-oxygen environment includes 150 mL / min, 600 mL / min or 2000 mL / min;

[0053] The assessment time includes 5h, 20h or 40h;

[0054] In some specific embodiments of the present invention, the water vapor flow rate comprises 1500 mL / min, and the oxygen flow rate comprises 500 mL / min; or

[0055] The water vapor flow rate includes 100 mL / min, and the oxygen flow rate includes 50 mL / min; or the water vapor flow rate includes 300 mL / min, and the oxygen flow rate includes 300 mL / min.

[0056] The present invention provides a micro-focus CT in-situ marking method, which can mark the local position of a micro-composite material and perform CT scanning on the position, and analyze the changes in structure and defects of the same position before and after high-temperature heat treatment.

[0057] The method includes a micro-focus CT sample stage capable of loading micro-composite material samples, a sample local position marking rod and a fixing method thereof. The micro-focus CT sample stage capable of loading micro-composite material comprises two independent cylindrical hollow spaces and a rectangular opening in the CT sample stage; the sample local position marking rod is in the shape of a rectangular parallelepiped; the CT sample stage and the sample local position marking rod are made of high temperature oxidation resistant materials such as aluminum oxide and silicon carbide; the gap positions of the samples in the two independent hollow spaces can be filled and fixed with a slurry prepared with resin and ceramic powder to fill the sample or the sample local position marking rod, and the slurry undergoes solidification and cracking reactions after heating and further reinforces the sample or the sample local position marking rod. After the CT sample stage and the sample or the sample local position marking rod are fixed, the position of the sample or the sample local position marking rod can be kept unchanged, thereby making it more convenient to perform micro-focus CT scanning processing. After the entire CT sample stage, the sample, and the sample local position marking rod are fixed, the sample can be tested in a high-temperature water-oxygen coupling environment and at different water-oxygen testing times, and the same position of the marked sample can be compared before and after the high-temperature water-oxygen testing.

[0058] The method has good versatility and can be used not only for micro composite materials, but also for analyzing and testing other solid samples such as ceramic-based composite materials. The present invention can mark the same position of the micro composite material, thereby realizing micro-focus CT scanning and analysis of the same position before and after the high-temperature water-oxygen test. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0060] Figure 1 The schematic diagram of loading samples on the sample stage of the CT equipment is shown;

[0061] Figure 2 Schematic diagram of the micro-focus CT in-situ labeling method;

[0062] Figure 3 The CT image of the SiCf / BN / SiC micro-composite material before oxidation is shown on the silicon carbide sample stage;

[0063] Figure 4 The CT image of the SiCf / BN / SiC micro-composite material loaded on the silicon carbide sample stage after oxidation for 20 hours is shown;

[0064] Figure 5The CT image of the SiCf / BN / SiC micro-composite material loaded on the silicon carbide sample stage after oxidation for 40 hours is shown;

[0065] Figure 6 Shows the pictures of SiCf / BN / SiC micro-composite materials before and after oxidation loaded on the graphite sample stage;

[0066] Figure 7 The CT image of the Cf / SiC ceramic matrix composite material before oxidation is shown on the silicon carbide sample stage;

[0067] Figure 8 The CT image of the silicon carbide sample stage loaded with Cf / SiC ceramic matrix composite material after oxidation is shown;

[0068] Fig. 9 The CT image of the SiCf / BN / SiC micro-composite material before oxidation is shown on the alumina sample stage;

[0069] Fig.10 Shows the CT image of the SiCf / BN / SiC micro-composite material after oxidation loaded on the alumina sample stage. DETAILED DESCRIPTION

[0070] The present invention discloses a microfocus CT in-situ marking device and method. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0071] The research on high-temperature thermal structural parts of ceramic-based composite materials needs to consider multiple factors such as temperature, time, and water-oxygen coupling environment. However, it takes a long time and is costly to directly study bulk ceramic-based composite materials. Since bulk ceramic-based composite materials are composed of multiple fiber bundles with different directions and arrangements, and the micro-composite specimens composed of a single fiber bundle and a matrix correspond to the basic scale of bulk composite materials, and the failure mechanism and damage law of unidirectional micro-composite materials in a high-temperature water-oxygen coupling environment are very similar to those of bulk composite materials, many scholars currently characterize their structure and performance in different high-temperature water-oxygen environments through micro-composite materials produced at a lower cost. Microfocus CT is an important means of observing and detecting the internal structure of ceramic-based composite materials. Therefore, in order to more accurately observe the internal structure changes occurring at the same position of the sample after high-temperature water-oxygen assessment, the present invention provides a microfocus CT in-situ marking method.

[0072] Explanation of relevant terms:

[0073] Microfocus CT: CT is computer tomography, which can be classified according to different criteria: nanofocus CT (test object 10-30μm, resolution 30-160nm), microfocus CT (test object 1-30mm, resolution 0.5-5μm), etc. It can perform three-dimensional imaging analysis without destroying the sample and reveal the internal three-dimensional structure of the sample.

[0074] In-situ marking: Mark the position of the sample, and scan the same position of the same sample each time; then compare the results of the two scans of the same position and observe the changes in the sample. The purpose of in-situ marking: For example, first mark a position and perform a CT scan to obtain CT image 1 of the sample before high temperature treatment; then perform high temperature treatment on the sample, perform a CT scan on the same position, and obtain CT image 2 of the sample after high temperature treatment. In this way, by analyzing and comparing images 1 and 2 obtained at the same position, it can be concluded what effect the high temperature treatment has on the sample.

[0075] The present invention provides a micro-focus CT in-situ marking method, which can mark the position of the sample, thereby more directly reflecting the impact of high-temperature water and oxygen on the material. The technical solution adopted by the present invention is as follows:

[0076] The invention provides a micro-focus CT in-situ marking method, and relates to the technical field of micro-composite material CT scanning detection.

[0077] The method comprises a micro-focus CT sample stage capable of loading a micro composite material sample, a sample local position marking rod and a fixing method thereof;

[0078] The micro-focus CT sample stage capable of loading micro-composite materials comprises two independent cylindrical hollow spaces and a rectangular opening in the CT sample stage, and the cylindrical hollow spaces and the rectangular opening penetrate the CT sample stage;

[0079] The method can mark the position of the sample from three angles: the sample stage, the opening, and the sample local marking rod;

[0080] The sample is fixed at the center of the sample stage, such as Figure 2 As shown in the position marked 1;

[0081] The rectangular opening can mark the position of the sample stage, such as Figure 2 As shown in the position marked 2;

[0082] The CT sample stage has a diameter of 10 to 20 mm, a thickness of 3 to 6 mm, and a diameter of the hollow space of the cylinder of 1 to 4 mm;

[0083] The sample local position marking rod is in the shape of a cuboid with a height of 5 to 15 mm. The sample local position marking rod can mark the height of the sample when it is scanned, such as Figure 2 As shown in the position marked 3;

[0084] The CT sample stage and the sample local position marking rod are made of high temperature oxidation resistant materials such as aluminum oxide and silicon carbide;

[0085] The gaps in the two independent hollow spaces can be filled and fixed with a slurry mixed with resin and ceramic powder to mark the sample or a local position of the sample;

[0086] The resin may be polycarbosilane and phenolic resin; the ceramic powder may be silicon carbide; the slurry mixing ratio of the resin to the ceramic powder is between 1:5 and 1:3;

[0087] The slurry preparation steps are: first weigh the resin and ceramic powder according to the proportion and then stir them evenly with a glass rod;

[0088] The slurry heating program can be heated at a rate of 10°C / min, at a temperature of 120°C, and for a holding time of 30min;

[0089] The slurry undergoes solidification and cracking reactions after being heated and further reinforces the sample or the local position marking rod of the sample;

[0090] After the CT sample stage is fixed to the sample or the sample local position marking rod, the positions of the sample and the sample local position marking rod can be kept unchanged, thereby making it more convenient to perform micro-focus CT scanning processing;

[0091] After the CT sample stage is fixed to the sample and the sample local position marking rod, the sample can be tested in a high-temperature water-oxygen coupling environment and at different water-oxygen testing times, and the same position of the marked sample can be compared before and after the high-temperature water-oxygen testing.

[0092] The high temperature range is 800-1200° C., the total flow rate of water vapor and oxygen in the water-oxygen environment is 150-2000 mL / min, and the insulation time is 1-40 hours.

[0093] In summary:

[0094] 1) The present invention can mark the same position of the micro-composite material from three perspectives: the ceramic slurry fixes the sample at the center of the sample stage, the opening marks the orientation, and the position marking rod marks the height.

[0095] 2) The high temperature oxidation resistance of the sample stage enables it to be subjected to high temperature heat treatment together with the sample, and enables micro-focus CT scanning and analysis of the same position of the material before and after high temperature water and oxygen testing.

[0096] The method provided by the present invention can fix the sample position and mark the scanning part of the sample in situ, so as to perform microfocus CT characterization on the sample in a more targeted manner; the sample stage and the sample position marking rod are resistant to high temperatures and can enter a high-temperature water-oxygen coupling environment with the sample, and perform multiple tests in the water-oxygen coupling environment, so as to observe the changes in the same position after multiple tests.

[0097] The raw materials and reagents used in the micro-focus CT in-situ marking device and method provided by the present invention can all be purchased from the market.

[0098] raw material:

[0099] SiCf / BN / SiC micro-composite material: Silicon carbide fiber (Cansas-3301 model, Fujian Jianya New Materials Co., Ltd.) is fixed on a tooling, placed in a high-temperature furnace, and the interface phase and matrix are prepared by chemical vapor infiltration process; specifically, it is placed in a CVI deposition furnace, evacuated to a vacuum degree below 200Pa, and then heated to 800-1500°C, and then the precursor gas is introduced at a flow rate of 5-15L / min, and the temperature is kept for 1-30h; after the insulation is completed, a protective gas is introduced into the furnace, and the temperature is naturally reduced to room temperature under the protective atmosphere, and it is taken out to obtain a SiCf / BN / SiC micro-composite material.

[0100] Cf / SiC ceramic-based composite material: Place carbon fiber (Japan Toray T300) in a precursor solution, evacuate to less than 100Pa, and impregnate for 1 to 5 hours. Transfer the impregnated carbon fiber to a high-temperature cracking furnace, heat it to 1100°C at a rate of 5°C / min, keep it warm for 1 hour, cool it down at a rate of 5°C / min, and use argon as the protective atmosphere. Repeat the above operation 1 to 3 times to prepare a Cf / SiC ceramic-based composite material.

[0101] Polycarbosilane: Institute of Chemistry, Chinese Academy of Sciences, model KH-VHPCS-1.

[0102] Phenolic resin: Wuxi Guangming Chemical Co., Ltd., 2130 phenolic resin.

[0103] Silicon carbide powder: Shanghai Xiangtian Nanomaterials Co., Ltd., 5μm.

[0104] The present invention will be further described below in conjunction with embodiments:

[0105] Example 1

[0106] This embodiment uses a micro-focus in-situ labeling method to scan and analyze samples that have been tested by high temperature water and oxygen. Figure 2As shown, the CT sample stage used in this method contains two independent cylindrical hollow spaces and a rectangular opening, and the cylindrical hollow space and the rectangular opening penetrate the CT sample stage. In this method, the position of the sample can be marked from three angles: the sample stage, the opening, and the sample local marking rod.

[0107] The sample can be fixed at the center of the sample stage, such as Figure 2 The rectangular opening can mark the position of the sample stage, as shown in the middle mark 1. Figure 2 As shown in the position of the middle mark 2; the diameter of the CT sample stage is 15mm, the thickness is 3mm, and the diameter of the cylindrical hollow space is 1mm; the sample local position marking rod is a rectangular parallelepiped with a height of 15mm; the sample local position marking rod can mark the height of the sample during scanning, such as Figure 2 As shown in the middle mark 3 position.

[0108] Among them, the CT sample stage and the sample local position marking rod are made of silicon carbide; the gap positions in the two independent hollow spaces contained in the CT sample stage can be filled and fixed with a slurry prepared by polycarbosilane and silicon carbide. After heating, the slurry undergoes solidification and cracking reactions to further strengthen the sample.

[0109] Among them, the slurry preparation ratio of polycarbosilane and silicon carbide is 1:4; the slurry preparation steps are: first weigh polycarbosilane (Institute of Chemistry, Chinese Academy of Sciences, model KH-VHPCS-1) and silicon carbide (Shanghai Xiangtian Nanomaterials Co., Ltd., 5μm) in proportion and then stir them evenly with a glass rod; the heating rate in the slurry heating program is 10℃ / min, the temperature is 120℃, and the insulation time is 30min; after heating, the slurry undergoes solidification and cracking reactions and further strengthens the sample and the sample local position marking rod; after the CT sample stage is fixed to the sample or the sample local position marking rod, the position of the sample or the sample local position marking rod can be kept unchanged, thereby making it more convenient to perform microfocus CT scanning processing.

[0110] In this embodiment, the sample is SiCf / BN / SiC micro-composite material. The preparation process of SiCf / BN / SiC micro-composite material is as follows: silicon carbide fiber (Cansas-3301 model of Fujian Jianli New Materials Co., Ltd.) is fixed on the tooling, placed in a high-temperature furnace, and the interface phase and matrix are prepared by chemical vapor infiltration process; specifically, it is placed in a CVI deposition furnace, evacuated to a vacuum degree of less than 200Pa in the furnace, and then heated to 800-1500°C, and then the precursor gas (BCl4 is a boron source, NH is a nitrogen source, CH3SiCl3 is a carbon source and a silicon source, and Ar is a diluent gas) is introduced at a flow rate of 5-15L / min, and the temperature is kept for 1-30h; after the insulation is completed, a protective gas (argon) is introduced into the furnace, and the temperature is naturally reduced to room temperature under the protective atmosphere, and taken out, that is, the SiCf / BN / SiC micro-composite material.

[0111] After the CT sample stage, the sample, and the sample local position marking rod are fixed, the scanning direction and the sample position mark height are recorded, and a micro-focus CT scan is performed on the sample. The scanning mode is bin2, the exposure time is 1 second, the voltage is 80kv, and the power is 10w in the air condition, and the CT scan of the sample before treatment is obtained. Figure 3 The sample stage loaded with the sample is then placed in an environment of high temperature 1100°C, water vapor 1500mL / min, and oxygen 500mL / min for assessment. After 20h and 40h of assessment, a micro-focus CT scan is performed on the same position marked on the sample to obtain the CT scan image after high temperature water and oxygen assessment. Figure 4 and Figure 5 shown.

[0112] Depend on Figure 3 It can be seen that the micro-composite material contains pores and defects before oxidation by taking a picture of a certain position after CT scanning. When tested in a high-temperature water-oxygen environment, water vapor and oxygen use the pores and cracks in the material as diffusion channels, thereby quickly oxidizing the material in a direction parallel to the fiber. Figure 4 and Figure 5 It can be observed that oxidation occurred at this position and porous oxidation products were produced, and the oxidation products increased with the increase of oxidation time.

[0113] Example 2

[0114] This embodiment uses a micro-focus in-situ labeling method to scan and analyze samples that have been tested by high temperature water and oxygen. Figure 2 As shown in FIG. 1 , the CT sample stage used in this method contains two independent cylindrical hollow spaces and a rectangular opening, and the cylindrical hollow space and the rectangular opening penetrate the CT sample stage. In this method, the position of the sample can be marked from three angles: the sample stage, the opening, and the sample local marking rod. Among them, the sample can be fixed at the center of the sample stage, such as Figure 2 The rectangular opening can mark the position of the sample stage, as shown in the middle mark 1. Figure 2 As shown in the position of the middle mark 2; the diameter of the CT sample stage is 15mm, the thickness is 3mm, and the diameter of the cylindrical hollow space is 3mm; the sample local position marking rod is a rectangular parallelepiped with a height of 15mm; the sample local position marking rod can mark the height of the sample during scanning, such as Figure 2 As shown in the middle mark 3 position.

[0115] Among them, the CT sample stage and the sample local position marking rod are made of graphite; the gap positions in the two independent hollow spaces contained in the CT sample stage can be filled and fixed with a slurry prepared by polycarbosilane and silicon carbide. After heating, the slurry undergoes solidification and cracking reactions to further strengthen the sample.

[0116] Among them, the slurry preparation ratio of polycarbosilane and silicon carbide is 1:4; the slurry preparation steps are: first weigh polycarbosilane and silicon carbide according to the proportion and then stir them evenly with a glass rod; the heating rate in the slurry heating program is 10°C / min, the temperature is 120°C, and the insulation time is 30min; after heating, the slurry undergoes solidification and cracking reactions and further strengthens the sample and the sample local position marking rod; after the CT sample stage and the sample or the sample local position marking rod are fixed, the position of the sample or the sample local position marking rod can be kept unchanged, thereby making it more convenient to perform microfocus CT scanning processing.

[0117] In this embodiment, the sample is SiCf / BN / SiC micro composite material. The preparation process of SiCf / BN / SiC micro composite material is the same as that of embodiment 1.

[0118] After the CT sample stage, sample, and sample local position marking rod are fixed, the sample stage loaded with the sample is placed in an environment with a high temperature of 1100°C, a water vapor of 500mL / min, and an oxygen of 500mL / min for 1 hour. The actual pictures before and after the high temperature water and oxygen test are obtained as shown below. Figure 6 shown.

[0119] Depend on Figure 6 It can be seen that after high temperature testing, the graphite sample stage and the local position marking rod disappeared, indicating that they were oxidized and reacted completely. Therefore, it can be seen that graphite material has poor high temperature oxidation resistance and is not suitable for preparing the sample stage in the present invention.

[0120] Example 3

[0121] This embodiment uses a micro-focus in-situ labeling method to scan and analyze samples that have been tested by high temperature water and oxygen. Figure 2 As shown, the CT sample stage used in this method contains two independent cylindrical hollow spaces and a rectangular opening, and the cylindrical hollow space and the rectangular opening penetrate the CT sample stage. In this method, the position of the sample can be marked from three angles: the sample stage, the opening, and the sample local marking rod.

[0122] The sample can be fixed at the center of the sample stage, such as Figure 2 The rectangular opening can mark the position of the sample stage, as shown in the middle mark 1. Figure 2 As shown in the position of the middle mark 2; the diameter of the CT sample stage is 20mm, the thickness is 4mm, and the diameter of the cylindrical hollow space is 4mm; the sample local position marking rod is a rectangular parallelepiped with a height of 12mm; the sample local position marking rod can mark the height of the sample during scanning, such as Figure 2 As shown in the middle mark 3 position.

[0123] Among them, the CT sample stage and the sample local position marking rod are made of silicon carbide; the gap positions in the two independent hollow spaces contained in the CT sample stage can be filled and fixed with a slurry prepared by phenolic resin and silicon carbide. After heating, the slurry undergoes solidification and cracking reactions to further strengthen the sample.

[0124] Among them, the slurry preparation ratio of phenolic resin and silicon carbide is 1:5; the slurry preparation steps are: first weigh phenolic resin (Wuxi Guangming Chemical Co., Ltd., 2130 phenolic resin) and silicon carbide according to the proportion and then stir them evenly with a glass rod; the heating rate in the slurry heating program is 10°C / min, the temperature is 120°C, and the insulation time is 30min; after heating, the slurry undergoes solidification and cracking reactions and further strengthens the sample and the sample local position marking rod; after the CT sample stage and the sample or the sample local position marking rod are fixed, the position of the sample or the sample local position marking rod can be kept unchanged, thereby making it more convenient to perform microfocus CT scanning processing.

[0125] In this embodiment, the sample is selected as Cf / SiC ceramic-based composite material. The preparation process of Cf / SiC ceramic-based composite material is as follows: carbon fiber (Japan Toray T300) is placed in a precursor solution (a mixed solution of polycarbosilane and diisopropylbenzene peroxide in a ratio of 1000:3), evacuated to less than 100Pa, and impregnated for 1 to 5 hours, and the impregnated carbon fiber is transferred to a high-temperature cracking furnace, heated to 1100°C at a rate of 5°C / min, kept warm for 1 hour, cooled at a rate of 5°C / min, and the protective atmosphere is argon; the above operation is repeated 1 to 3 times to prepare Cf / SiC ceramic-based composite material.

[0126] After the CT sample stage, the sample, and the sample local position marking rod are fixed, the scanning direction and the sample position mark height are recorded, and a micro-focus CT scan is performed on the sample. The scanning mode is bin2, the exposure time is 1 second, the voltage is 80kv, and the power is 10w in the air condition, and the CT scan of the sample before treatment is obtained. Figure 7 ; Then the sample stage loaded with the sample is placed in an environment of high temperature 800°C, water vapor 100mL / min, and oxygen 50mL / min for assessment. After 40 hours of assessment, a micro-focus CT scan is performed on the same position marked on the sample to obtain a CT scan image after high temperature water and oxygen assessment. Figure 8 shown.

[0127] Depend on Figure 7 It can be seen that by taking a picture of a certain position of the Cf / SiC ceramic matrix composite material after CT scanning, it can be seen that the micro-composite material before oxidation contains pores and defects. Figure 8 It can be seen that after the high-temperature water-oxygen environment test, oxidation was found to have occurred at this location, oxidation of the carbon fiber on the surface was observed, and the defects of the material tended to become larger.

[0128] Example 4

[0129] This embodiment uses a micro-focus in-situ labeling method to scan and analyze samples that have been tested by high temperature water and oxygen. Figure 2 As shown, the CT sample stage used in this method contains two independent cylindrical hollow spaces and a rectangular opening, and the cylindrical hollow space and the rectangular opening penetrate the CT sample stage. In this method, the position of the sample can be marked from three angles: the sample stage, the opening, and the sample local marking rod.

[0130] The sample can be fixed at the center of the sample stage, such as Figure 2 The rectangular opening can mark the position of the sample stage, as shown in the middle mark 1. Figure 2 As shown in the position of the middle mark 2; the diameter of the CT sample stage is 10mm, the thickness is 6mm, and the diameter of the cylindrical hollow space is 3mm; the sample local position marking rod is a rectangular parallelepiped with a height of 5mm; the sample local position marking rod can mark the height of the sample during scanning, such as Figure 2 As shown in the middle mark 3 position.

[0131] Among them, the CT sample stage and the sample local position marking rod are made of alumina; the gap positions in the two independent hollow spaces contained in the CT sample stage can be filled and fixed with a slurry prepared by polycarbosilane and silicon carbide. After heating, the slurry undergoes solidification and cracking reactions to further strengthen the sample.

[0132] Among them, the slurry preparation ratio of polycarbosilane and silicon carbide is 1:3; the slurry preparation steps are: first weigh polycarbosilane and silicon carbide according to the proportion and then stir them evenly with a glass rod; the heating rate in the slurry heating program is 10°C / min, the temperature is 120°C, and the insulation time is 30min; after heating, the slurry undergoes solidification and cracking reactions and further strengthens the sample and the sample local position marking rod; after the CT sample stage and the sample or the sample local position marking rod are fixed, the position of the sample or the sample local position marking rod can be kept unchanged, thereby making it more convenient to perform microfocus CT scanning processing.

[0133] In this embodiment, the sample is SiCf / BN / SiC micro composite material. The preparation process of SiCf / BN / SiC micro composite material is the same as that of embodiment 1.

[0134] After the CT sample stage, the sample, and the sample local position marking rod are fixed, the scanning direction and the sample position mark height are recorded, and a micro-focus CT scan is performed on the sample. The scanning mode is bin2, the exposure time is 1 second, the voltage is 80kv, and the power is 10w in the air condition, and the CT scan of the sample before treatment is obtained. Fig. 9Then the sample stage loaded with the sample is placed in an environment with a high temperature of 1200°C, 300mL / min of water vapor and 300mL / min of oxygen for assessment. After 1 hour of assessment, a micro-focus CT scan is performed on the same position marked on the sample to obtain a CT scan image after high temperature water and oxygen assessment. Fig.10 shown.

[0135] Depend on Fig. 9 It can be seen that the micro-composite material before oxidation contains pores and defects when the image of a certain position of the SiCf / BN / SiC micro-composite material is taken after CT scanning. Fig.10 It can be seen that after the high-temperature water-oxygen environment test, it was found that oxidation occurred at this location and porous oxides were generated inside.

[0136] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Micro-focus in-situ marking device, characterized in that: The micro-focus in-situ marking device comprises a sample local position marking rod and a micro-focus CT sample stage; The material of the sample local position marking rod includes but is not limited to a material that is resistant to high temperature oxidation; the shape of the sample local position marking rod includes but is not limited to a cuboid; the number of the sample local position marking rods includes at least 1; the height of the sample local position marking rod includes 5 to 15 mm; The material of the micro-focus CT sample stage includes but is not limited to a material resistant to high temperature oxidation; the micro-focus CT sample stage includes an independent hollow space and an opening; the diameter of the micro-focus CT sample stage includes 10 to 20 mm, and the thickness includes 3 to 6 mm; The microfocus CT sample stage, the opening and the sample local position marking rod mark the position of the sample from three angles; The sample is fixed at the center of the microfocus CT sample stage; The opening marks the position of the microfocus CT sample stage; The sample local position marking rod marks the height of the sample when it is scanned; The independent hollow space and the opening penetrate the microfocus CT sample stage; The number of the independent hollow spaces includes at least 2; the shape of the independent hollow spaces includes a cylinder; the diameter of the independent hollow spaces includes 1 to 4 mm; The number of the openings is at least 1; the shape of the openings is a rectangular parallelepiped.

2. The micro-focus in-situ marking device according to claim 1, characterized in that: The material of the sample local position marking rod includes but is not limited to aluminum oxide or silicon carbide; The height of the sample local position marking rod includes 5mm, 12mm or 15mm; The material of the microfocus CT sample stage includes but is not limited to aluminum oxide or silicon carbide; The diameter of the microfocus CT sample stage includes 10 mm, 15 mm or 20 mm, and the thickness includes 3 mm, 4 mm or 6 mm; The diameter of the independent hollow space includes 1mm, 3mm or 4mm; Preferably, the diameter of the microfocus CT sample stage is 10 mm and the thickness is 6 mm; or The diameter of the microfocus CT sample stage is 20 mm or less, and the thickness is 4 mm or less; or The diameter of the microfocus CT sample stage is 15 mm, and the thickness is 3 mm.

3. Application of the micro-focus in-situ marking device according to claim 1 or 2 in any of the following: (I), micro-focus in situ labeling; and / or (II) characterizing the structure and / or properties of the composite material; The composite material includes but is not limited to a micro-composite material or a ceramic-based composite material; The structure and / or performance of the composite material includes but is not limited to the structure and / or performance of the composite material at the same position before and after being subjected to high temperature and / or water-oxygen environment assessment; The high temperature ranges from 800 to 1200° C.; the total flow rate of water vapor and oxygen in the water-oxygen environment ranges from 150 to 2000 mL / min; and the assessment time ranges from 1 to 40 hours.

4. The use according to claim 3, characterized in that The micro composite material includes but is not limited to SiCf / BN / SiC micro composite material; the ceramic matrix composite material includes but is not limited to Cf / SiC ceramic matrix composite material; The high temperature includes 800°C, 1100°C or 1200°C; the total flow rate of water vapor and oxygen in the water-oxygen environment includes 150mL / min, 600mL / min or 2000mL / min; the test time includes 5h, 20h or 40h; Preferably, the water vapor flow rate includes 1500 mL / min, and the oxygen flow rate includes 500 mL / min; or the water vapor flow rate includes 100 mL / min, and the oxygen flow rate includes 50 mL / min; or the water vapor flow rate includes 300 mL / min, and the oxygen flow rate includes 300 mL / min.

5. Microfocus CT in-situ labeling method, characterized in that: Based on the device according to claim 1 or 2, the method comprises the following steps: Step 1, inserting the sample and the sample local position marking rod into the independent hollow space of the microfocus CT sample stage respectively, filling the gap position in the independent hollow space with slurry, heating, causing curing and / or cracking reaction, and fixing the sample and / or the sample local position marking rod to the microfocus CT sample stage respectively; Step 2, recording the scanning position and the height of the position mark of the sample, performing micro-focus CT scanning, and obtaining a CT scan image of the sample before processing; Step 3, placing the sample in a high temperature and / or water-oxygen environment for assessment, and performing a micro-focus CT scan on the same position of the sample mark according to the scanning orientation and the sample position mark height recorded in step 2 to obtain a CT scan image after assessment; The high temperature includes 800 to 1200° C.; the total flow rate of water vapor and oxygen in the water-oxygen environment includes 150 to 2000 mL / min; the assessment time includes 1 to 40 hours; Step 4: Compare the CT scan image of the sample before treatment obtained in step 2 with the CT scan image after assessment obtained in step 3, and analyze.

6. The microfocus CT in-situ marking method according to claim 5, characterized in that: The ingredients of the slurry in step 1 include resin and ceramic powder; the ratio of the resin to the ceramic powder is 1:5 to 1:3; Preferably, the ratio of the resin to the ceramic powder includes 1:3, 1:4 or 1:5; The slurry preparation step includes: weighing the resin and the ceramic powder according to a proportion and stirring them evenly; The resin includes but is not limited to polycarbosilane or phenolic resin; the ceramic powder includes but is not limited to silicon carbide.

7. The microfocus CT in-situ marking method according to claim 5, characterized in that: The heating rate in step 1 includes but is not limited to 10°C / min, the heating temperature includes but is not limited to 120°C, and the time for which the microfocus CT sample stage is placed at the temperature includes but is not limited to 30 minutes; The sample in step 1 comprises a composite material; The composite material includes but is not limited to a micro-composite material or a ceramic-based composite material; Preferably, the micro-composite material includes but is not limited to SiCf / BN / SiC micro-composite material; Preferably, the ceramic-based composite material includes but is not limited to Cf / SiC ceramic-based composite material.

8. The microfocus CT in-situ marking method according to claim 5, characterized in that: The scanning orientation in step 2 includes the position of the sample in the X-axis direction marked by the center of the microfocus CT sample stage and the position of the sample in the Y-axis direction marked by the opening; the position mark height of the sample includes the position of the sample in the Z-axis direction marked by the sample local position mark rod, so as to realize the position of the sample marked at three angles; The parameters of the microfocus CT scan in step 2 include: scanning mode bin2, exposure time 1 second, voltage 80 kV and power 10 W in air.

9. The method according to claim 5, characterized in that The high temperature in step 3 includes 800° C., 1100° C. or 1200° C.; The total flow rate of water vapor and oxygen in the water-oxygen environment includes 150 mL / min, 600 mL / min or 2000 mL / min; The assessment time includes 5h, 20h or 40h.

10. The method according to claim 9, characterized in that The water vapor flow rate comprises 1500 mL / min, and the oxygen flow rate comprises 500 mL / min; or The water vapor flow rate comprises 100 mL / min, and the oxygen flow rate comprises 50 mL / min; or The water vapor flow rate includes 300 mL / min, and the oxygen flow rate includes 300 mL / min.